Pepperoni pizza can be murder - Cavender, Chris (Cavender, Chris. Pizza lovers mystery., 2010)
After the body of her delivery driver's brother ends up on the floor of her pizzeria, Eleanor Swift enlists the help of her sister Maddy in searching for the real killer, all while trying to keep her pizza business afloat.